2009
DOI: 10.1037/a0015659
|View full text |Cite
|
Sign up to set email alerts
|

Collective efficacy, group potency, and group performance: Meta-analyses of their relationships, and test of a mediation model.

Abstract: The authors examined relationships among collective efficacy, group potency, and group performance. Meta-analytic results (based on 6,128 groups, 31,019 individuals, 118 correlations adjusted for dependence, and 96 studies) reveal that collective efficacy was significantly related to group performance (.35). In the proposed nested 2-level model, collective efficacy assessment (aggregation and group discussion) was tested as the 1st-level moderator. It showed significantly different average correlations with gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
335
1
14

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 380 publications
(388 citation statements)
references
References 106 publications
(89 reference statements)
18
335
1
14
Order By: Relevance
“…In team settings, meta-analytic reviews have demonstrated that collective efficacy has a medium to strong effect on team performance (Gully, Incalcaterra, Joshi, & Beaubien, 2002;Stajkovic, Lee, & Nyberg, 2009) and therefore we might also expect team attributions to influence team performance through changes in collective efficacy. Activation and variation in testosterone levels have also been shown to predict decisions to compete again (Mehta & Josephs, 2006), levels of cooperation (Mehta, Wuehrmann, & Josephs, 2009) and approachavoidance behaviours (Mehta, Jones, & Josephs, 2008).…”
Section: Mediating Relationshipsmentioning
confidence: 99%
“…In team settings, meta-analytic reviews have demonstrated that collective efficacy has a medium to strong effect on team performance (Gully, Incalcaterra, Joshi, & Beaubien, 2002;Stajkovic, Lee, & Nyberg, 2009) and therefore we might also expect team attributions to influence team performance through changes in collective efficacy. Activation and variation in testosterone levels have also been shown to predict decisions to compete again (Mehta & Josephs, 2006), levels of cooperation (Mehta, Wuehrmann, & Josephs, 2009) and approachavoidance behaviours (Mehta, Jones, & Josephs, 2008).…”
Section: Mediating Relationshipsmentioning
confidence: 99%
“…Arguably collective efficacy has been the most salient efficacy belief investigated in team contexts (Gully et al 2002;Stajkovic et al 2009;Goncalo et al 2010;Budworth 2011). …”
Section: Team Contextmentioning
confidence: 99%
“…Findings from empirical studies (including metaanalysis) have found that collective efficacy predicts team performance (Gully et al 2002;Stajkovic et al 2009), and mediates the training-performance relationship (Brown 2003;Budworth 2011). An interesting study involving undergraduate teams (Goncalo et al 2010) found that 'premature' emergence of collective efficacy can have adverse effects, such as suppressing the discussion of alternative ideas during team problem-solving.…”
Section: Team Contextmentioning
confidence: 99%
“…It is a jointly-held belief in the group's ability to succeed in general -at any task or challenge the group may face. Group potency is positively correlated with collective success (Stajkovic, Lee & Nyberg, 2009) and has been demonstrated to be a reliable predictor of performance in semi-autonomous, self-managed teams (de Jong, de Ruyter & Wetzels, 2005). In a sales-specific context, Rego, Junior, and Cunha (2015) found that group potency explains sales performance over and above other potential explanatory variables (e.g., authentic leadership and group virtuousness).…”
Section: Work Group Inputsmentioning
confidence: 99%
“…This is a distinctly different construct than group potency, because the non-specificity of task or challenge is the key difference between the concept of group potency and the related but distinct construct of collective efficacy (which is task-or domain-specific): group potency assesses a group's joint-held belief in the likelihood of success in general, while collective efficacy is a group's jointly held belief in the likelihood of success in a specific task or functional domain (Stajkovic, Lee, & Nyberg, 2009 Jex and Bliese (1999).…”
Section: Work Group Inputsmentioning
confidence: 99%